2015
DOI: 10.1177/2053434515620223
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of care for patients with COPD: Clinical points of interest

Abstract: The management of care of chronic obstructive pulmonary disease improved over the last years but is still very complex. Both over-and underdiagnosis are often reported and misclassification of disease severity is common. Differentiating between chronic obstructive pulmonary disease, asthma and asthma-chronic obstructive pulmonary disease overlap syndrome remains difficult. Much is known about the effectiveness of treatment approaches in chronic obstructive pulmonary disease, but patients are often not treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Physicians should stimulate and evaluate adherence to therapy. Therapy adherence can be increased by raising awareness with the patient of the disease and by improving care cooperation [49] between different healthcare providers and patients [50]. To evaluate adherence, questionnaires can be filled out in the waiting room.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Physicians should stimulate and evaluate adherence to therapy. Therapy adherence can be increased by raising awareness with the patient of the disease and by improving care cooperation [49] between different healthcare providers and patients [50]. To evaluate adherence, questionnaires can be filled out in the waiting room.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Moreover, a major challenge of eHealth in care coordination is to make it beneficial and easy to use for health care providers and patients, otherwise neither will use it [24]. Also, online self-management support needs to be a fully integrated element of IDM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous eHealth studies have revealed the challenges, barriers, and factors that make successful implementation difficult, yet many questions remain unanswered. Moreover, a major challenge of eHealth in care coordination is to make it beneficial and easy to use for health care providers and patients, otherwise neither will use it [ 24 ]. Also, online self-management support needs to be a fully integrated element of IDM.…”
Section: Introductionmentioning
confidence: 99%
“…Although patient attitudes and receptiveness toward eHealth applications are promising in certain groups of age and education [ 22 , 23 , 24 ], large-scale adoption of eHealth in daily practice still lags behind predictions in comparison with the explosive growth of other digital tools like Facebook and Twitter [ 25 ] (also, during recent years, online banking acceptance has increased rapidly worldwide [ 26 ]). A major challenge of eHealth in care coordination is to make it beneficial and easy to use for both health care providers and patients [ 27 ]. It is important that online self-management support is a fully integrated element of IDM; COPD and asthma patients tended to use an online application on a regular basis when the caregiver was involved, whereas patients on their own used the application only sporadically [ 28 ].…”
Section: Introductionmentioning
confidence: 99%